Three-Dimensional Reconstruction of Arterial-Lymphatic Vascular Complex (Vessel Within the Vessel) in Breast Tissue - Ivan Ivanov; Savelina Popovska; Emilian Ivanov; Sergey Iliev; Pencho Tonchev (Journal of Biomedical & Clinical Research)
The phenomenon “vessels within vessels” was initially described by Merchant S et al. as arteries found free-floating inside the lumen of veins. We have described another version of the “vessels within vessels”complex, composed of arteries found inside the lumen of lymphatic vessels. The purpose of the present study was to describe the structure of the lympho-arterial vascular complex in a breast tissue specimen from a male subject using three- dimensional tissue reconstruction. A histological specimen from a 64 year-old male subject diagnosed with gynecomastia was used. The tissue sample was sectioned in a multi-step manner. An overall of approximately 150pm thick tissue material was sampled. Immunostaining with anti-CD34 antibody and anti-podoplanin antibody was performed. Three-dimensional reconstruction of the vessel within the vessel structure was performed with “Reconstruct” software When the reconstruction of the breast parenchyma was revealed as a 3D image, it became apparent that the arterial vessel was situated inside the lymphatic vessel and could be followed along the entire length of the vascular segment studied. We have proved that these vascular complexes are not artificial phenomenon and do exist. The function of the vascular complexes is still uncertain, and is probably related to lymph propulsions in the initial collector vessels.